IMPLEMENTATION OF RELATIONSHIP PATTERNS WITH THE VILLAGE CONSULTANCY BOARD (BPD) AND THE VILLAGE GOVERNMENT IN LALABATA VILLAGE, TANATE RILAU DISTRICT, BARRU REGENCY - Hj. Aidah; Salmawati (Meraja journal, 2021)
Copyright (c) 2021 Meraja journal